A tree‐ring width based drought reconstruction for southeastern China: links to Pacific Ocean climate variability. (30th December 2015) - Chen, Feng; Yu, Shulong; Yuan, Yujiang; Wang, Huiqin; Gagen, Mary
Abstract : We present a drought reconstruction for southeastern China based on a tree‐ring width chronology of Cryptomeria fortunei developed from two sampling sites in central Fujian. A reconstruction of July–February drought variability, spanning AD 1855–2011, was developed by calibrating total tree‐ring width data with the self‐calibrating Palmer drought severity index (scPDSI). The reconstruction was verified against an independent data set, and accounts for 36% of the actual scPDSI variance during the period 1955–2011. Relatively dry intervals were reconstructed between AD 1859–1880, 1899–1911, 1927–1933, 1946–1959, 1964–1970 and 1987–1997. Relatively wet conditions prevailed during 1855–1858, 1881–1898, 1912–1926, 1934–1945, 1960–1963, 1971–1986 and 1998–2011. Comparisons between our scPDSI reconstruction and a moisture‐sensitive tree‐ring width record from Vietnam revealed consistencies between the two data sets, suggesting similar drought regimes. Spectral peaks of 2.2–6.4 years may be indicative of El Niño‐Southern Oscillation (ENSO) activity, as also suggested by the significant correlations with sea surface temperatures (SSTs) in the eastern equatorial and southeastern Pacific Ocean and an extreme event analysis. The analysis of links between our scPDSI reconstruction and the large‐scale regional climatic variation shows that there is a relationship between regional drought variation and East Asian summer monsoon (EASM) intensity.